A revision of Rhynchoglossum (Gesneriaceae) in Malesia - Abdulrokhman Kartonegoro (Reinwardtia, 2013)
The genus Rhynchoglossum in Malesia has been revised. Five species are included: R. borneense, R. capsulare, R. klugioides, R. obliquum and R. spumosum. Rhynchoglossum obliquum is a widespread and common species while the other four are endemic to Malesia. Morphological descriptions, nomenclature, distribution, ecological information and notes are provided for all species. An identification key and a list of examined specimens are included.